Definitive Healing Through Simplicity - Evaluating Draining Seton Alone in the Management of Fistula-in-Ano: Outcomes in Healing and Postoperative Morbidity - Khan, Rafiul Karim; Islam, Md Rashidul; Lima, Ismat Jahan; Bahar, Mejbahul; Talukdar, Monoarul Islam; Sarker, Rajib Dey (Journal of Shaheed Suhrawardy Medical College, 2025)
Background: The prime goal and challenge in combating fistula-in-ano is to achieve complete tract closure while preserving continence. Surgical techniques vary based on fistula complexity and surgeon expertise, with conventional methods like fistulotomy and fistulectomy posing a risk of incontinence, particularly in high trans-sphincteric cases. Low trans-sphincteric fistulas are generally amenable to fistulotomy, whereas SETON placement has long served as a drainage-focused, sphincter-sparing alternative. This technique facilitates abscess resolution and promotes tract healing through controlled inflammation. Result: In this study, we encountered 30 patients with fistula-in-ano who were treated with draining seton, the mean age was 41.5 ± 12.2 years, with a male predominance (83.3%). The majority of patients (76.7%) achieved complete healing, while 23.3% showed no improvement. Postoperative complications were minimal, with 9.9% experiencing pain, 3.3% reporting bleeding, and 3.3% developing incontinence, indicating draining seton as a highly effective and well-tolerated treatment option. Conclusion: This study demonstrated that draining seton achieved favourable outcomes in the treatment of fistula-in-ano, with the majority of patients experiencing complete healing. The overall complication rate remained low, with minimal occurrences of pain, bleeding, and incontinence. These findings position draining seton as a highly effective and well-tolerated therapeutic approach for fistula-in-ano. J Shaheed Suhrawardy Med Coll 2024; 16(1): 58-63